Effect of dislocation density on optical gain and internal loss of AlGaN-based ultraviolet-B band lasers. (31st March 2020) - Tanaka, Shunya; Kawase, Yuta; Teramura, Shohei; Iwayama, Sho; Sato, Kosuke; Yasue, Shinji; Omori, Tomoya; Iwaya, Motoaki; Takeuchi, Tetsuya; Kamiyama, Satoshi; Akasaki, Isamu; Miyake, Hideto
Abstract: We investigated the dependence of the lasing threshold power density, optical gain, and internal loss on the dislocation density of an optically pumped AlGaN-based ultraviolet-B band laser. Reducing the dislocation density was found to not only increase the optical gain by reducing the non-radiative recombination centers but also reduce the internal loss. Furthermore, this reduction in internal loss was appropriately explained using an increased scattering model based on an increase in the refractive index fluctuations formed by the dislocations.